2009
DOI: 10.17221/52/2009-cjas
|View full text |Cite
|
Sign up to set email alerts
|

The effect of transport on biochemical and haematological indices of common carp (Cyprinus carpio L.)

Abstract: ABSTRACT:The effect of 12 h transport on the biochemical and haematological profiles of three-years-old common carp was investigated. There was a significant increase (P < 0.01) in ammonia, chloride, phosphorus, lactate dehydrogenase, aspartate aminotransferase and creatine kinase, and a significant decrease (P < 0.05) in total proteins. The levels of glucose (P < 0.01), lactate (P < 0.05), alanine aminotransferase (P < 0.01) and calcium (P < 0.01) were also significantly changed, but no time-dependent relatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
20
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(27 citation statements)
references
References 27 publications
7
20
0
Order By: Relevance
“…However, the erythrocytes counts obtained from HSD and LSD groups fell within erythrocyte count range provided by Bittencourt et al (2003) for Nile tilapia. The rise in red blood cell numbers in fish held at HSD is similar to patterns described in previous studies (Montero et al 2001;Bittencourt et al 2003;Dobšikova et al 2009;Abdel-Tawwab 2012) in which stress enhanced the numbers of erythrocytes. Falcon et al (2007) observed that stress lead to elevation of the levels of cortisol that in turn lead to increased erythropoietin concentration stimulating erythrocytes production.…”
Section: Effect Of Stocking Density On Plasma Cortisol Level Blood Gsupporting
confidence: 88%
See 1 more Smart Citation
“…However, the erythrocytes counts obtained from HSD and LSD groups fell within erythrocyte count range provided by Bittencourt et al (2003) for Nile tilapia. The rise in red blood cell numbers in fish held at HSD is similar to patterns described in previous studies (Montero et al 2001;Bittencourt et al 2003;Dobšikova et al 2009;Abdel-Tawwab 2012) in which stress enhanced the numbers of erythrocytes. Falcon et al (2007) observed that stress lead to elevation of the levels of cortisol that in turn lead to increased erythropoietin concentration stimulating erythrocytes production.…”
Section: Effect Of Stocking Density On Plasma Cortisol Level Blood Gsupporting
confidence: 88%
“…In this study, cortisol could have induced increase in glucose and erythrocytes. Cortisol typically promotes mobilization of glucose from energy-rich substrates by depletion of hepatic glycogen stores, and its reallocation to different tissues (Schreck et al 2001;Dobšikova et al 2009). …”
Section: Effect Of Stocking Density On Plasma Cortisol Level Blood Gmentioning
confidence: 99%
“…Hematological profiles have often been used as stress indicators (Dobšikova et al, 2009). Major shifts in the haemogram are found in fish exposed to acute or chronic stress.…”
Section: Discussionmentioning
confidence: 99%
“…Liver damage caused by these pollutants was correlated with the activities of certain plasma enzymes, such as CK, ALT, AST, ALP, LDH (Malbrouck et al, 2003), and meanwhile, the secondary toxic effect on basic metabolism was indicated by the alterations of levels of blood NH 3 , GLU and TP (Zhang et al, 2008b). Therefore, the biochemical parameters of blood plasma are useful in monitoring the physiological status of fish and as indicators of the aquatic environmental health (Rehulka and Parova, 2000;Rehulka and Minarik, 2001;Dobšíková et al, 2009).…”
mentioning
confidence: 99%